A Memory Net Structure: Present Implementation and a Proposed Language - Shapiro, Stuart C. (University of Wisconsin-Madison Department of Computer Sciences, 1968)
A memory net structure has been designed which is particularly useful for storing, processing, and retrieving information of the type used in semantic analysis of natural language, question answering and theorem proving. The net consists of blocks, or items, each one of which may be an unstructured unit or may represent a structure consisting of an ordered pair or triple of items. Any given structure (or unstructured unit) in the memory is represented by exactly one item no matter how many other structures make use of it as a substructure. Any item may be associated with an external print name. The structures are built using symmetric links so that all structures which use a given item are reachable from that item. Procedures to manipulate this net and some to use it in a question answering system have been programmed in Burroughs B5500 Extended ALGOL, also making use of ASLIP, a SLIP like package of list processing procedures. A net manipulating programming language is proposed whose basic data units are the items and structures of this net, just as the basic dat units of a list processing language are elements and lists.